Reassessment of Non-Monosynaptic Excitation from the Motor Cortex to Motoneurons in Single Motor Units of the Human Biceps Brachii - Nakajima, Tsuyoshi; Tazoe, Toshiki; Sakamoto, Masanori; Endoh, Takashi; Shibuya, Satoshi; Elias, Leonardo A.; Mezzarane, Rinaldo A.; Komiyama, Tomoyoshi; Ohki, Yukari (Frontiers in Human Neuroscience, 2017)
orticospinal excitation is mediated by polysynaptic pathways in several vertebrates, including dexterous monkeys. However, indirect non-monosynaptic excitation has not been clearly observed following transcranial electrical stimulation (TES) or cervicomedullary stimulation (CMS) in humans. The present study evaluated indirect motor pathways in normal human subjects by recording the activities of single motor units (MUs) in the biceps brachii (BB) muscle. The pyramidal tract was stimulated with weak TES, CMS, and transcranial magnetic stimulation contralateral to the recording side. During tasks involving weak co-contraction of the BB and hand muscles, all stimulation methods activated MUs with short latencies. Peristimulus time histograms showed that responses with similar durations were induced by TES (1.9 ± 1.4 ms) and CMS (2.0 ± 1.4 ms), and these responses often showed multiple peaks with the peristimulus time histogram peak having a long duration (65.3% and 44.9%, respectively). Such long-duration excitatory responses with multiple peaks were rarely observed in the finger muscles following TES or in the BB following stimulation of the Ia fibers. The responses obtained with TES were compared in the same 14 BB MUs during the co-contraction and isolated BB contraction tasks. Eleven and three units, respectively, exhibited activation with multiple peaks during the two tasks. In order to determine the dispersion effects on the axon conduction velocities and synaptic noise, a simulation study that was comparable to the TES experiments was performed with a biologically plausible neuromuscular model. When the model involved only a monosynaptic pyramidal tract pathway, multiple peaks were obtained in about 34.5% of the motoneurons. However, the percentage almost doubled when monosynaptic pathways were included in the simulation, and these results were similar to the results of the human experiments. The experimental and simulation results indicated the existence of task-dependent disparate inputs from the pyramidal tract to the motoneurons of the upper limb. These results suggested that intercalated interneurons are present in the spinal cord and that these interneurons might be equivalent to those identified in animal experiments.